The Returns to Job Search: A Test of Two Models - Kahn, Lawrence M. (The Review of Economics and Statistics, 1978)
T HEORETICAL work on job search views unemployment as productive search activity. By remaining unemployed, a worker acquires labor market information that helps him/ her maximize lifetime utility. Different models have different predictions with regard to the relation between search time and the resulting wage. For example, under one set of assumptions, the expected resulting wage may increase with increasing search time, while under a different set of assumptions, the relationship may be negative. These two possibilities imply differing relationships of the job searcher to the labor market. In the first case (increasing expected resulting wage), the worker weighs a typical offer against the high probability that a better one will come along later. In the second case (decreasing expected resulting wage), because future offers are likely to be worse than the typical present offer, the worker is more likely than otherwise to take whatever job is available. This paper estimates the relationship between search time and resulting wage. A simultaneous equations framework is used in which search time is endogenous (as well as the resulting wage). It is found that the expected resulting wage declines as search time increases. This result is consistent with the ranking by a searcher of firms according to expected wage offers, with the high wage firms sampled first (Salop, 1973). Further, the determinants of the duration of unemployment are investigated by race-sex groups.